If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(y + -1) = 13 + -1y Reorder the terms: 5(-1 + y) = 13 + -1y (-1 * 5 + y * 5) = 13 + -1y (-5 + 5y) = 13 + -1y Solving -5 + 5y = 13 + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add 'y' to each side of the equation. -5 + 5y + y = 13 + -1y + y Combine like terms: 5y + y = 6y -5 + 6y = 13 + -1y + y Combine like terms: -1y + y = 0 -5 + 6y = 13 + 0 -5 + 6y = 13 Add '5' to each side of the equation. -5 + 5 + 6y = 13 + 5 Combine like terms: -5 + 5 = 0 0 + 6y = 13 + 5 6y = 13 + 5 Combine like terms: 13 + 5 = 18 6y = 18 Divide each side by '6'. y = 3 Simplifying y = 3
| 2m^2-9m-35=0 | | 6(x+5)=-36 | | 4x-5(x+3)=23 | | 25-(x+7)=6x-3 | | 8-4x=-2x-4 | | 3(15x+5)-15=3(15x-15)+3 | | 9-(4+5)= | | -2x-4(-2x-2)=-10 | | 15(8-3)-64=x | | 6x+4=4x+26 | | -4x-7+6x=-6 | | 5a-2c+7=(6a-3c+2) | | -6(a+9)=-24+4a | | -6-x=-3x-2 | | p=21 | | -3-2p=-3(p+2) | | 9(y-1)=11-y | | 6-3(-0.4)=-18(-0.4) | | 9+3y=-24 | | 5a-2c+7-(6a-3c+2)=0 | | 21=7x-14 | | 3+4n+5n=21 | | 2(y-20)=10-3y | | 4(z+2)-2z=10+3(a-3) | | 8y-7-10y=-19 | | 4x+8=2x+18 | | 8(8+7)+3(5-1)=x | | 7(5+n)=3(n+1) | | 12-4(y-4)=3y | | Q-16=-48 | | 4x+6-7(10x+4)= | | -7x+21+9x+21=6 |